2004
DOI: 10.1186/1471-5945-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Vitamin D increase mRNA levels for the growth control hIK1 channel in human epidermal keratinocytes but functional channels are not observed

Abstract: Background: Intermediate-conductance, calcium-activated potassium channels (IKs) modulate proliferation and differentiation in mesodermal cells by enhancing calcium influx, and they contribute to the physiology of fluid movement in certain epithelia. Previous reports suggest that IK channels stimulate proliferative growth in a keratinocyte cell line; however, because these channels indirectly promote calcium influx, a critically unique component of the keratinocyte differentiation program, an alternative hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Furthermore, to elucidate the role of the BK channel in cell proliferation of ventricular fibroblasts, we carried out cell proliferation assay, and found that it was increased by clotrimazole (a specific IK channel blocker), but not by IBTX (a specific BK channel blocker) or apamin (a specific SK channel blocker) during 24 hr of incubation. Our results on IK channels are in good accordance with previous observation that 1-EBIO (a specific IK activator) suppresses mRNA expression of IK channels and cell proliferation in HaCaT kerationcytes (Koegel et al, 2003) and C6 glioma cell lines (Manaves et al, 2004). However, activation of IK channels with 1-EBIO increases T lymphocytes proliferations, whereas inhibition of the channel with clotrimazole decreases proliferation (Khanna et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, to elucidate the role of the BK channel in cell proliferation of ventricular fibroblasts, we carried out cell proliferation assay, and found that it was increased by clotrimazole (a specific IK channel blocker), but not by IBTX (a specific BK channel blocker) or apamin (a specific SK channel blocker) during 24 hr of incubation. Our results on IK channels are in good accordance with previous observation that 1-EBIO (a specific IK activator) suppresses mRNA expression of IK channels and cell proliferation in HaCaT kerationcytes (Koegel et al, 2003) and C6 glioma cell lines (Manaves et al, 2004). However, activation of IK channels with 1-EBIO increases T lymphocytes proliferations, whereas inhibition of the channel with clotrimazole decreases proliferation (Khanna et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…EBIO activates K Ca 3.1 with an EC 50 of 24-80 μM, however, it also activates K Ca 2 channels with an EC 50 of 87 μM [5]. Non-specific effects of EBIO have also been reported by Manaves et al [17] who demonstrated that EBIO inhibited keratinocyte proliferation, suggesting that K Ca 3.1 could be anti-proliferative. However, this antiproliferative effect was not blocked by charybdotoxin, clotrimazole, or TRAM-34 leading the authors to conclude that EBIO inhibited proliferation by other mechanisms besides K Ca 3.1 activation, i.e.…”
Section: K Ca 31 Blockers and Activatorsmentioning
confidence: 80%
“…These results seem to suggest that the IK Ca channel expression is subject to the same (differentiation) signals controlling GFAP expression. Moreo- ver, a number of studies report that IK Ca channels are downregulated during differentiation in tumor and normal models (C6 rat glioma cells [23]; the keratinocyte cell line HaCaT [32]; myogenic cell lines [50,51]; promielocytes during granulocytic differentiation [21]), although in few cases an upregulation of the IK Ca channel expression has been observed following differentiation [52,53].…”
Section: Modulation Of the Ik Ca Channelsmentioning
confidence: 99%